Applicability of a single‐use bioreactor compared to a glass bioreactor for the fermentation of filamentous fungi and evaluation of the reproducibility of growth in pellet form - Soerjawinata, Winda; Schlegel, Konstantin; Fuchs, Natalie; Schüffler, Anja; Schirmeister, Tanja; Ulber, Roland; Kampeis, Percy (Engineering in life sciences, 2021)
The implementation of single‐use technologies offers several major advantages, e.g. prevention of cross‐contamination, especially when spore‐forming microorganisms are present. This study investigated the application of a single‐use bioreactor in batch fermentation of filamentous fungus Penicillium sp. (IBWF 040‐09) from the Institute of Biotechnology and Drug Research (IBWF), which is capable of intracellular production of a protease inhibitor against parasitic proteases as a secondary metabolite. Several modifications to the SU bioreactor were suggested in this study to allow the fermentation in which the fungus forms pellets. Simultaneously, fermentations in conventional glass bioreactor were also conducted as reference. Although there are significant differences in the construction material and gassing system, the similarity of the two types of bioreactors in terms of fungal metabolic activity and the reproducibility of fermentations could be demonstrated using statistic methods. Under the selected cultivation conditions, growth rate, yield coefficient, substrate uptake rate, and formation of intracellular protease‐inhibiting substance in the single‐use bioreactor were similar to those in the glass bioreactor.